(untitled) (Revista de Medicina Clinica, 2022)
Introduction: The use of the ROX index in COVID-19 patients allows evaluating those with a high risk of ventilatory failure, however, it has not been openly validated in patients who use a mask with a Hudson-type reservoir. Patients and Methods: retrospective study of 306 adults infected with SARS-CoV2 by antigenic or molecular test. The main objective was to evaluate the role of the ROX index as a predictor of respiratory failure and mortality. In the inferential statistical analysis, the odds ratios OR with their confidence intervals greater than 95% will be used as association measures. Qualitative variables were evaluated using the Chi-square test or Fisher’s exact test, and in the case of numerical or quantitative variables, the Student’s t-test or Mann-Whitney test was used. Results: The highest frequency in male gender 78% and female 22%, the ROX values were higher in survivors at 2 h 5.8 (4.7 - 6.9), in relation to the deceased 4.5 (3.6 - 5 .6). Similarly, at 12 h the values were higher in the group of survivors 7.8 (5.2 - 8.7) in relation to the deceased 4.9 (3.8 - 6.0). The age- and gender-adjusted odds ratio of the ROX index was 8.5, CI (2.0 - 91.4) at 2 h and 17.6, CI (2.8 - 93.6) at 12 h. Conclusions: The ROX index in this study has proven to be a reliable evaluator of mortality in COVID-19, studies with larger groups of patients are required to validate the results found here.